Pembuatan LKPD berbasis model learning cycle 7E pada materi hukum newton tentang gerak, usaha dan energi untuk pembelajaran fisika kelas X SMA/MA - andrizal andrizal; gusnedi gusnedi (PILLAR OF PHYSICS EDUCATION, 2019)
Good education is an increase in the quality of education that is inseparable from the improvement in the competence of students. The purpose of national education is for students' competencies, both in terms of attitudes, knowledge and skills. The effort made by the government is to develop the curriculum from KTSP 2006 to the 2013 curriculum and revise it. Based on the results of the interview, there are many obstacles in the learning process. Implementation in the learning process of teachers still uses the lecture method, lack of use of LKPD in the learning process, lack of implementation of practicum activities in schools, teaching materials used are less attractive to students and not contains steps of activities that must be carried out by students. Therefore, researchers are interested in conducting research that aims to produce LKPD based on Learning Cycle 7E models that are tested for validation. The type of research used is Research and Development (R&D). R & D research methods are research methods used to produce certain products. This research procedure consisted of potential problems, data collection, product design, design validation, and design revision. Product design validation was carried out by three expert lecturers. The components assessed are content worthiness, language, presentation and graphics. The results of the validation of LKPD were 83.67%. Overall LKPD based on Learning Cycle 7E model is in a very valid category so it is suitable to be used in physics learning.